2015
DOI: 10.1149/2.0801503jes
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Study of Pyrargyrite in Acid Media

Abstract: Silver antimony sulfide (Ag 3 SbS 3 , pyrargyrite) was synthesized by a solid state route from silver, antimony and sulfur powder precursors under an argon atmosphere. The product was characterized by powder X-ray diffraction (XRD) and found to be Ag 3 SbS 3 pyrargyrite alone, with a bandgap (E g ) of 2.0 eV. We analyzed the ground sample by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). The bulk composition was found to be consistent with stoichiometric ratios. Surface char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…24,25 It has wide applications in nonlinear optics and photocatalysts. 24,26 To our best knowledge, there has been no reports on the application of Ag 3 SbS 3 as a solar absorber material (preliminary photoelectrochemical study of Ag 3 SbS 3 has been explored, but no photovoltaic data were reported 27 ). Ag 3 SbS 3 nanoparticles, thin films and nanorods have been synthesized by hydrothermal, soft-chemical, polyol-mediated, chemical deposition and biomolecule-assisted methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 It has wide applications in nonlinear optics and photocatalysts. 24,26 To our best knowledge, there has been no reports on the application of Ag 3 SbS 3 as a solar absorber material (preliminary photoelectrochemical study of Ag 3 SbS 3 has been explored, but no photovoltaic data were reported 27 ). Ag 3 SbS 3 nanoparticles, thin films and nanorods have been synthesized by hydrothermal, soft-chemical, polyol-mediated, chemical deposition and biomolecule-assisted methods.…”
mentioning
confidence: 99%
“…24,25 It has wide applications in nonlinear optics and photocatalysts. 24,26 To our best knowledge, there has been no reports on the application of Ag 3 SbS 3 as a solar absorber material (preliminary photoelectrochemical study of Ag 3 SbS 3 has been explored, but no photovoltaic data were reported 27 ).…”
mentioning
confidence: 99%